Finnish Centre of Excellence in Physics, Chemistry, Biology and Meteorology of Atmospheric Composition and Climate Change : summary and outlook - Kulmala, Markku; Lappalainen, Hanna K.; Back, Jaana; Laaksonen, An; Nikinmaa, Eero; Riekkola, Marja-Liisa; Vesala, Timo; Viisanen, Yrjo; Aalto, Tuula; Boy, Michael; Dal Maso, Miikka; Ehn, Mikael; et al. (Finnish Environment Institute, 2016)
Peer reviewed